Comparative genomic analysis reveals a high prevalence of inter-species in vivo transfer of carbapenem-resistance plasmids in patients with haematological malignancies - Kocer, Kaan; Boutin, Sébastien; Dalpke, Alexander; Heeg, Klaus; Mutters, Nico T.; Nurjadi, Dennis (Clinical microbiology and infection, 2020)
Objectives - Conjugative gene transfer has been considered as one of the driving factors in the transmission and dissemination of multidrug resistance in bacteria. The abundance of antimicrobial resistance genes and bacteria in the gut microbiome may provide the ideal platform for plasmid exchange. Systematic data on in vivo horizontal gene transfer (HGT) and its frequency are scarce. - Materials and methods - One hundred and ninety-six carbapenem-resistant gram-negative bacilli (CRGNBs) from 179 patients (158 inpatients and 21 outpatients) between January 2016 and April 2017 were analysed retrospectively. Alignment of plasmid content for 32 isolates from 16 patients with multiple CRGNB species was performed from whole-genome sequencing (WGS) data. - Results - Sixteen of the 179 patients (8.9%) were colonized and/or infected with more than one CRGNB species; 11/179 (6.1%) were colonized by multiple carbapenem-resistant Enterobacteriaceae (CREs) and 5/179 (2.8%) by carbapenem-resistant non-fermenters (CRNFs) and CREs. WGS suggested interspecies transfer as the predominant mechanism rather than independent acquisition in 8/10 patients (80%, one non-recoverable isolate) with multiple CREs but not in CRNF-CRE combinations; 30/158 inpatients (20%) had underlying haematological malignancies, and they are more likely to exhibit multiple CRGNB strains (OR 3.0, 95%CI 0.98-8.89, p 0.05) and CRE strains (OR 3.9, 95%CI 1.02-14.58, p 0.04) during hospital stay compared to other patient groups. - Conclusion - Our data give insight into the occurrence of natural in vivo HGT in a clinical setting. Better understanding of HGT will help optimize containment measures and may guide antibiotic stewardship programmes.